Drosophila Imaginal Discs as a Model of Epithelial Wound Repair and Regeneration - Smith-Bolton, Rachel (Adv Wound Care (New Rochelle), 2016)
Significance: The Drosophila larval imaginal discs, which form the adult fly during metamorphosis, are an established model system for the study of epithelial tissue damage. The disc proper is a simple columnar epithelium, but it contains complex patterning and cell-fate specification, and is genetically tractable. These features enable unbiased genetic screens to identify genes involved in all aspects of the wound response, from sensing damage to wound closure, initiation of regeneration, and re-establishment of proper cell fates. Identification of the genes that facilitate epithelial wound closure and regeneration will enable development of more sophisticated wound treatments for clinical use. Recent Advances: Imaginal disc epithelia can be damaged in many different ways, including fragmentation, induction of cell death, and irradiation. Recent work has demonstrated that the tissue's response to damage varies depending on how the wound was induced. Here, we summarize the different responses activated in these epithelial tissues after the different types of damage. Critical Issues: These studies highlight that not all wounds elicit the same response from the surrounding tissue. A complete understanding of the various wound-healing mechanisms in Drosophila will be a first step in understanding how to manage damaged human tissues and optimize healing in different clinical contexts. Future Directions: Further work is necessary to understand the similarities and differences among an epithelial tissue's responses to different insults. Ongoing studies will identify the genes and pathways employed by injured imaginal discs. Thus, work in this genetically tractable system complements work in more conventional wound-healing models.